1995
DOI: 10.1021/j100041a050
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Melting Transitions of Rod-like Molecules Analyzed by Reflection-Absorption Infrared Spectroscopy

Abstract: The melting of ordered monolayers of n-hexane, n-octane, and n-decane adsorbed on Pt( 11 1) has been studied by reflection-absorption infrared spectroscopy (RAIRS). Each alkane forms an overlayer at low temperatures (< 160 K) that is characterized by both quasi-long-range translational and orientational order. Previous lowenergy electron diffraction (LEED) studies suggested that the alkanes are arranged on the surface in the all-trans conformation, and this has been confirmed by RAIRS. The low-temperature orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
92
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(105 citation statements)
references
References 13 publications
11
92
1
1
Order By: Relevance
“…The NN and NNN atomic distance of the Au-(111) surface in the compressed direction is 0.277 and 0.486 nm, respectively. The adsorption of alkanes with molecular axis along NN(90) is expected to be more favorable if one considers that the NN atomic distance in this direction is closer to the C-C-C zigzag length than that in NN (30). The experimental results presented here, however, do not agree with this expectation.…”
Section: Resultscontrasting
confidence: 68%
“…The NN and NNN atomic distance of the Au-(111) surface in the compressed direction is 0.277 and 0.486 nm, respectively. The adsorption of alkanes with molecular axis along NN(90) is expected to be more favorable if one considers that the NN atomic distance in this direction is closer to the C-C-C zigzag length than that in NN (30). The experimental results presented here, however, do not agree with this expectation.…”
Section: Resultscontrasting
confidence: 68%
“…5B, even at the same v. This fact argues that the overall impingement and the rate of impingement have an impact on nucleation/growth and annealing processes (i.e., Stages 1-4). These data, which are paralleled by the wetting and electrochemical measurements pre- 2965 2956 2935 2925 2909 2878 2859 1 Assignments and orientations from [10,36,105]. a \ to the CH 3 -CH 2 bond in the C-C-C plane.…”
Section: Irrasmentioning
confidence: 60%
“…Demuth et al [66], Hoffmann et al [67] and Avery [68] reported C-H mode softening for C 5 and C 6 cycloalkanes adsorbed on ruthenium, nickel and platinum. Hostetler et al report unusually sharp, softened C-H stretching modes for n-octane on Pt(1 1 1) obtained with IR [69].…”
Section: Resultsmentioning
confidence: 99%